Wavelength-Multiplexed Duplex Transceiver Based on III-V/Si Hybrid Integration for Off-Chip and On-Chip Optical Interconnects - Kaixuan Chen; Qiangsheng Huang; Jianhao Zhang; Jianxin Cheng; Xin Fu; Chenzhao Zhang; Keqi Ma; Yaocheng Shi; Dries Van Thourhout; Gunther Roelkens; Liu Liu; Sailing He (IEEE Photonics Journal, 2016)
A six-channel wavelength-division-multiplexed optical transceiver with a compact footprint of 1.5 × 0.65 mm2 for off-chip and on-chip interconnects is demonstrated on a single silicon-on-insulator chip. An arrayed waveguide grating is used as the (de)multiplexer, and III-V electroabsorption sections fabricated by hybrid integration technology are used as both modulators and detectors, which also enable duplex links. The 30-Gb/s capacity for each of the six wavelength channels for the off-chip transceiver is demonstrated. For the on-chip interconnect, an electrical-to-electrical 3-dB bandwidth of 13 GHz and a data rate of 30 Gb/s per wavelength are achieved.